The ability to speak English of the local tour guides for promoting tourism at the Aceh Tsunami Museum - Sofyan Abdul Gani; Cut Intan Damayanti (Studies in English Language and Education, 2018)
This research aimed to find out the English language proficiency of the local tour guides at the Aceh Tsunami Museum, Aceh, Indonesia, and the difficulties that they faced in communicating with foreign tourists in English. A quantitative and qualitative descriptive research design was utilized to collect data in which an English proficiency test and an interview were used as instruments. The research subjects were 13 local guides working in the Aceh Tsunami Museum. Based on the results from this research, it was found that virtually all the participating tour guides were in the categories of very good, good and average.  However, they still experienced problems with several aspects of speaking EFL, such as expressing ideas verbally, poor collocations i.e. incorrect or inappropriate word choices, poor pronunciation, and lack of confidence when speaking English. It is expected that the results from this research will become a useful input for the management of English Education institutions for improving their instructional systems and for tour guides to continue learning and developing their communication skills, especially their oral English communication skills.